"Продовольчі експедиції" та"авоська": споживчі пристрасті "homo sovieticus" у сучасній прозі - Даниленко, Людмила Вікторівна; Danylenko, L. V. (My University, 2021)
У статті розглянуто питання споживчих інтересів радянської люди-ни на прикладі творів О. Ільченка «Збирачі туманів» і С. Батурина «Шизґара». Пояснено художні ідеї розвінчання міфів про добробут гро-мадян СРСР, проаналізовано панораму повсякденного життя в умовах продовольчого дефіциту, простежено суголосність авторських інтер-претацій як достовірність змалювання пережитого. Зазначено, що відтворення сутності уніфікованої моделі «homo sovieticus» виявляє нікчемність і небезпечність тоталітарної системи, нівелює можли-вість ностальгійних «зітхань»за радянським минулим. Contemporary Ukrainian prose has been actively appealing to the memory of the Soviet past recently. Especially interesting is the literary reconstruction of everyday life that creates a background for demonstrating a specifi c type of ‘homo sovieticus’. A discussion on this large-scale and promising process has already started within liter-ary studies. Th e paper deals with O. Ilchenko’s “Fog Pickers” and S. Baturyn’s “Shyzgara”, which represent the everyday life of Kyiv in the Soviet era. Th e focus is on the literary treatment of consumerism as a feature of a unifi ed model representing the Soviet man.Th e researcher explains the ideas of debunking the myths about happy life in the USSR, analyzes the ways of creating the panoramic view of everyday life, traces the consistency of the authors’ interpretations that shows how accurately the experiences are depicted. Th e gastronomic routes of Kyiv residents, the methods of obtaining the foodstuff s, the social relationships established during purchases presented in the literary works are worth special attention. Th e writers are defi nitely critical regarding everyday living conditions in the re-cent past. Th ey put characteristic features of the Soviet everyday life at the center of events, namely the lines in the stores of all kinds and their primitive range of products. Some Soviet euphemisms related to the food theme have been explained in the paper as well.Th e researcher comes to the conclusion that reconstruction of the everyday life of a Soviet man in the works by O. Ilchenko and S. Baturyn reveals the despicable nature and danger of the totalitarian system, shows the groundlessness of the nostalgic gasps for the Soviet Union. Th e literary representation of life in the USSR prompts one to refl ect on the true values and uphold human dignity in a free state.
“Food expeditions” and “avoska”: consumer passions of “homo sovieticus” in the modern prose
Keywords: художня реконструкція; адянське минуле; повсякдення; іронія; сарказм; literary reconstruction; Soviet past; everyday life; irony; arcasm